Uma Metodologia para a Construção Semiautomatizada de Ontologias a partir de Documentos Textuais - MATOS, Hellen Carmo de Oliveira (2009)
Information organization became a fundamental process in face of the exponential increasing of available information, motivated by technology advances, Internet in particular. It demands effective approaches of information filtering and searching, like the information retrieval systems. Such systems depend on the document s semantic representation, which can be implemented through conceptual and semantic relationship representation instruments, as ontologies. The ontology construction is a complex and time-consuming process. It s difficult to know whether a given ontology is wide enough to represent the documents semantic information. Up to date ontologies are developed according to Ontology Engineering standards and methods, although there is no any universal solution. This work presents a methodology for semi-automatic construction of ontologies. It also demonstrates an ontology construction for grid computing domain, aiming to validate the proposal. Such domain is strongly associated to resources sharing to solve problems on dynamic and heterogeneous environment. The allocation of these resources is an essential task in the grid and depends on the quality of available information. The constructed ontology aims to provide a description of the resources available in a computational grid to help on the qualification of information contained in this environment. This will allow the semantic discovery of grid resources to run applications on an efficient way